Mendeteksi Kecurangan Laporan Keuangan Dengan Menggunakan Analisis Rasio Keuangan - Lyta, Yurike Ester; Suwandi, Suwandi (Universitas Muhammadiyah Gresik, 2024)
The aim of this research is to test financial ratios as a tool for detecting fraudulent financial statements. This research uses the monitoring premise of agency theory to explain the association between financial ratios and financial statement fraud. Proxies for measuring financial ratios include four financial ratios, namely debt ratio, profitability, cash flow and accruals. Financial reporting fraud uses an occurrence-based proxy, namely a dummy for regulatory violations in sample companies. The samples tested were manufacturing companies registered on the IDX during 2016-2018. The results of this research show that empirically financial ratios are not yet fully capable of being used to detect fraudulent financial statements.